Seeking a sanctuary: Seventh-day Adventism and the American dream - Bull, Malcolm (Harper & Row, 1989)
This is the first book to reveal the variety and significance of the Adventist experience. It analyzes Adventism's theological heritage, development, and social institutions. Unlike the Mormons and the Jehovah's Witnesses, Adventists have never gained notoriety through open opposition to the state, nor are they part of the Protestant mainstream that sustains the national religious identity. In spite of its being one of the most important religious movements native to the United State, Seventh-day Adventism has been widely misunderstood. Its organizational and financial structure, evangelistic success, attitude toward health, dealings with the state, and the character of its art all reveal its ambiguous position in American society and its deviant response to the American dream. As America offered sanctuary to generation of immigrants from Europe, so Adventism sought to provide sanctuary from America. By presenting itself as an alternative to the Republic, the church rapidly came to operate as an alternative to America in the social sphere as well, as Adventists replicated the institutions and functions of American society. In all these aspects, Adventism seems ambiguous. Bull and Lockhart argue that the very ambiguity of Adventism's relationship to America is the source of its identity and success. - Preface. Acknowledgments. 1. Introduction: Public Images.PART ONE: Adventist Theology. 2. Authority. 3. Identity. 4. The End of the World. 5. The Divine Realm. 6. The Human Condition. 7. The Development of Adventist Theology.PART TWO: The Adventist Experience and the American Dream. 8. The Structure of Society. 9. The Patters of Growth. 10. The Science of Happiness. 11. The Politics of Liberty. 12. The Art of Expression. 13. Adventism and America.PART THREE: Adventist Subculture. 14. Women. 15. Blacks. 16. Ministers. 17. Doctors. 18. Educators. 19. The Self-Supporting Movement. 20. Conclusion: The Revolving Door. Abbreviations. Notes. Bibliographical Note. Index